Pengembangan Media Pembelajaran Ular Tangga Berbasis Digital pada Mata Pelajaran IPS - Tiara Agustin; Frima, Aren; Rosalina, Elya (IJOCE: Indonesia Journal of Civic Education, 2026)
This research aims to develop digital-based learning media for snakes and ladders in social studies subjects for class V at SD Negeri 53 Lubuklinggau that is valid, practical and effective. The method used is R&D using the ADDIE model, with research subjects namely experts, teachers and class V students at SD Negeri 53 Lubuklinggau. Data collection in research was carried out by observation, interviews, questionnaires and tests. The instruments used are in the form of questionnaires and written questions. The research results show that the product developed is valid with an average validity of 0.89 and the analysis of the practicality sheet assessment for educators and students meets the very practical criteria with an average of 94.81%. Then analysis of the effectiveness assessment obtained an N-Gain score with an average of 0.73 in the high category. Based on the research results, it can be concluded that the Digital-Based Learning Media Snakes and Ladders for Class V Social Sciences Subjects at SD Negeri 53 Lubuklinggau has proven to be valid, practical and effective so that it is suitable for use in Class V Social Sciences learning at SD Negeri 53 Lubuklinggau.   Keywords: Digital, Social Sciences, Development, Elementary School, Snakes and Ladders